2011
DOI: 10.1007/s00040-011-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

Paternally inherited alleles in male body parts of an ant (Diacamma sp.) sex mosaic: implication for androgenetic male production in the Hymenoptera

Abstract: Sex mosaicism, also called gynandromorphism, refers to an accidental phenomenon in dioecious organisms (mainly animals) in which an individual phenotype includes both female and male characteristics. Despite the rarity of this phenomenon, elucidating the mechanisms of naturally occurring sex mosaicism should deepen our understanding of diverse sex determination and differentiation systems in nature. We report the results of a genetic study of a sex mosaic individual of the ant Diacamma sp. from Japan's Okinawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The available evidence for the emergence of gynandromorphs with several different parental origins, such as the androgenetic and gynogenetic ones, potentially leading to evolutionary novelties, comes from the studies of social Hymenoptera, emphasizing the range of developmental variants that can potentially lead to an evolutionary novelty. It has been hypothesized that some of these developmental variants, for example androgenetic male production, might share the same underlying cytogenetic mechanism with gynandromorphism (Yoshizawa et al 2009;Dobata et al 2012;Aamidor et al 2018). Our study implies that the gynogenetic origin of a gynandromorph is possible in solitary Hymenoptera as well.…”
Section: Morphologysupporting
confidence: 52%
See 1 more Smart Citation
“…The available evidence for the emergence of gynandromorphs with several different parental origins, such as the androgenetic and gynogenetic ones, potentially leading to evolutionary novelties, comes from the studies of social Hymenoptera, emphasizing the range of developmental variants that can potentially lead to an evolutionary novelty. It has been hypothesized that some of these developmental variants, for example androgenetic male production, might share the same underlying cytogenetic mechanism with gynandromorphism (Yoshizawa et al 2009;Dobata et al 2012;Aamidor et al 2018). Our study implies that the gynogenetic origin of a gynandromorph is possible in solitary Hymenoptera as well.…”
Section: Morphologysupporting
confidence: 52%
“…Gynandromorphy is a developmental abnormality, resulting in chimaeric individuals, which combine patches of both genetically female-and male-type tissues (Narita et al 2010). Their generation is thought to be associated with the sex-determination systems, and study of this phenomenon broadens our current knowledge of the evolutionary mechanisms driving the diverse sex determination and differentiation systems (Narita et al 2010;Yang and Abouheif 2011;Dobata et al 2012;Aamidor et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, if gynandromorphy goes 'all the way', as it were, then we would have a case of androgenesis. It is, therefore, appropriate to consider species where gynandromorphy occurs spontaneously and at high frequency as a possible evolutionary route to androgenesis, and to explore the factors that increase the frequency of gynandromorphy [65]. Although factors increasing gynandromorphy are poorly understood, new insights could be developed from comparative studies as gynandromorphs are regularly reported across a broad range of Hymenoptera, including bees (e.g.…”
Section: Androgenesis In Gynandromorphs and Other Mosaicsmentioning
confidence: 99%
“…Nevertheless, if gynandromorphy goes 'all the way', as it were, then we would have a case of androgenesis. It is, therefore, appropriate to consider species where gynandromorphy occurs spontaneously and at high frequency as a possible evolutionary route to androgenesis, and to explore the factors that increase the frequency of gynandromorphy [65].…”
Section: Androgenesis In Gynandromorphs and Other Mosaicsmentioning
confidence: 99%
“…Colonies have no morphological queen caste, and a mated worker, called a gamergate [21], reproduces as the functional queen. Each colony has, at most, a single gamergate (monogynous) that is usually singly mated (monandrous) ( [22], but see also [23]). Reproductive specialization occurs at the adult stage by social manipulation [22].…”
Section: Materials and Methods (A) Ant Speciesmentioning
confidence: 99%